(untitled) (Al-Academy, 2019)
In the theory of cinema genre, horror films are at the forefront of the list. It is one of the oldest genres that saw the light with the early emergence of cinema, taking advantage of literary works, especially Gothic literature and it continues to this day, but the third millennium has seen a marked increase in the number of films and recipients alike. There were many types within the same genre and there are many authors and varied topics, all seeking to spread terror and panic and fear in the hearts of viewers who are passionate about the type of horror. Although the fear and horror have been, throughout the ages, a challenge to the psychological balance and stability, as well as being a rejection and an opposition to the aesthetic taste and hostile to all that is beautiful, joyful and valuable, yet it still appears in many practices of reception as a captivating aesthetic value, able to influence the souls and conscience, and attract many viewers. The increase in the production of horror movies and their viewers is conclusive evidence of the existence of this trend in many recipients of both sexes